ANALYSIS OF STUDENT LEARNING DIFFICULTIES IN SUBJECT EDUCATIONAL PHILOSOPHY IN INFORMATICS CLASS MEDAN TECHNOLOGY INSTITUTE - A. Zebar (Universitas Negeri Medan, 2018)
Abstract : Analysis Of Students Learning Difficulties In Educational Philosophy Subject In Informatics Class Medan Technology Institute.The number of students who have difficulty in studying the philosophy of education is the main reason that makes writers interested in this problem. The subjects used for the research are Student Class Informatics Institute of Technology Medan with the number of 28 people. The method used is questionnaire method in the form of questionnaire. The results obtained that the difficulties of students in the lecture of educational philosophy is influenced by several factors namely factors of lecturer, student, learning time, the subject used and the influence of the lecture of educational philosophy towards educational system.Keywords : Learning Difficulties, Educational Philosophy, Method QuestionnaireAbstrak: Analisis Kesulitan Belajar Mahasiswa Pada Materi Filsafat Pendidikan Di Kelas Informatika Institut Teknologi Medan. Banyaknya mahasiswa yang kesulitan dalam mempelajari filsafat pendidikan adalah alasan utama yang membuat penulis tertarik dengan masalah ini. Subjek yang dijadikan untuk penelitianya itu Mahasiswa Kelas Informatika Institut Teknologi Medan dengan jumlah 28 orang. Metode yang digunakan adalah metode kuisioner dalam bentuk angket. Diperoleh hasil bahwa kesulitan mahasiswa dalam mata kuliah filsafat pendidikan dipengaruhi oleh beberapa factor yaitu factor dari dosen, mahasiswa, waktu pembelajaran, bahan pembelajaran yang digunakan dan pengaruh dari mata kuliah filsafat pendidikan terhadap system pendidikan.Kata Kunci : Kesulitan Belajar, Filsafat Pendidikan, Metode Kuisioner